2018
DOI: 10.1002/hed.25465
|View full text |Cite
|
Sign up to set email alerts
|

Functional fat injection under local anesthesia to treat severe postsurgical dysphagia, case report

Abstract: Background: In this study, we present the first application of functional fat injection performed under local anesthesia in the treatment of severe dysphagia secondary to head and neck cancer surgery. Methods: Functional fat injection was performed using a transcervical approach. Control of injection depth and site was performed through a transnasal flexible endoscope. The effect of surgery was evaluated through videofluoroscopy (VFS), Fiberendoscopic Evaluation of Swallowing (FEES), Functional Oral Intake Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Martin-Harris and colleagues have investigated the effect of a respiratory-swallowing training in patients with head and neck cancer treated with different modalities and chronic dysphagia and have reported an improvement in the laryngeal closure and the tongue base retraction, associated with a reduction of lower airways’ invasion and pharyngeal residue [36]. As for laryngeal closure, fat injections have been proposed in patients who underwent an OPHL type I for the correction of the tissue loss at the level of the base of tongue, with promising results on the improvement of the swallowing efficiency [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Martin-Harris and colleagues have investigated the effect of a respiratory-swallowing training in patients with head and neck cancer treated with different modalities and chronic dysphagia and have reported an improvement in the laryngeal closure and the tongue base retraction, associated with a reduction of lower airways’ invasion and pharyngeal residue [36]. As for laryngeal closure, fat injections have been proposed in patients who underwent an OPHL type I for the correction of the tissue loss at the level of the base of tongue, with promising results on the improvement of the swallowing efficiency [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…These three studies showed that lipofilling might be an effective treatment for HNC patients with chronic dysphagia. No complications were reported, and therefore, lipofilling seems safe [38,49,50]. Many patients showed improved objective and subjective swallowing function after lipofilling.…”
Section: Short-term Outcomesmentioning
confidence: 86%
“…In the last few years, different studies, primarily case reports, have been published about the use of lipofilling in patients with chronic dysphagia due to HNC (treatment) [38,49,50]. Navach et al [49] reported about a 58-year-old patient with impaired swallowing after treatment for a nasopharyngeal carcinoma.…”
Section: Short-term Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Crary et al (7) originally suggested the adult FOIS for stroke patients. Afterwards, other researchers expanded the FOIS for patients with traumatic brain injury (31, 32), head and neck cancer (33, 34), vocal fold immobility (35), vagal schwannoma resection (36), cerebral palsy (37), postsurgical dysphagia (38), neurodegenerative diseases (39), postextubation dysphagia in children (40), and neurogenic dysphagia (41). The FOIS for infants suggested in the present study was a simplified scale with levels reduced from 7 to 5, without taking into account the concepts of single/multiple consistency food, special preparation or compensation, and food restriction.…”
Section: Study Limitationsmentioning
confidence: 99%